The feasibility of micro‐ultrasound as a tool to image peripheral nerves. (29th November 2016) - Chandra, A.; Eisma, R.; Felts, P.; Munirama, S.; Corner, G. A.; Demore, C. E. M.; McLeod, G.
Summary: Despite widespread use of ultrasound imaging to guide needle placement, the incidence of transient and permanent nerve damage as a complication of regional anaesthesia has not changed over the last decade. In view of the controversy surrounding intraneural injection there is a need to understand the structural changes caused by subepineural and subperineural needle penetration. Clinical ultrasound machines do not provide adequate anatomical resolution, and anaesthetists have difficulty judging the precise location of the needle tip relative to the epineurium. We studied the suitability of micro‐ultrasound imaging (which offers anatomical resolution better than 100 μm) as a tool for viewing neural anatomy and deformation caused by needle insertion. The primary objective was to assess micro‐ultrasound imaging as a method to view fascicles within nerves resected from fresh and soft‐embalmed cadavers. Secondary objectives were to observe any disruption of the neural anatomy caused by anaesthetic needle penetration, and to assess the integrity of fresh and Thiel method soft‐embalmed nerves, after handling and during needle insertion using ultrasound images and histology. We imaged nine nerves from the left and right sides of fresh and soft‐embalmed cadavers. A regional block needle was inserted into three median nerves. We identified fascicles > 0.4 mm in width using micro‐ultrasound. Subepineural needle placement was associated with denting, rotation and elastic deformation of fascicles, whereas subperineural needle insertion split fascicles permanently.